Против течения: [роман] / Евгения Перова - Перова Евгения Георгиевна (Счастье мое, постой!, 2017)
Экземпляры: (20230130) / Инвентарный номер: 40152 / Цена: 266.40 / Сис.шифр: 84(2=411.2)6 / Авт.знак: П 27 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44